Estimation of border effect on yield of rice and nutrient uptake - MAK Mian (International Journal of Agricultural Science and Food Technology - Peertechz Publications, 2021)
The experiment was conducted at Agronomy Research Field of Bangladesh Agricultural Institute, Gazipur during 2019 to quantify the border effect on rice. The experiment was set in a randomized complete block design with twelve replications. The treatment was non border (T1) and border (T2). Border treatment (T2) had significant and positive influence on different parameters of rice. Grain yield and associated yield components improved in border treatment. Border effect was estimated at 8% in respect of grain yield. Increased tillers/hill (18%), filled grains/panicle (47%), grain weight/panicle (45%), grain growth (12%) weight of 1000-grain (0.97%), biological yield (4%) and harvest index (4.5%) were observed in border rows. Rice plant both flowered and matured 3 days earlier in border rows. Carbon input and uptake of N, P, K, S and Zn by rice were found higher values in border treatment. Carbon accumulation increased about 4.4% in border rice. Two lines/rows of rice hill should be excluded for harvesting of plot yield. Otherwise 8% yield will be deducted in actual yield calculation for eliminating the border area effect/border effect (for 2 lines/rows of hills around the plot).